Water Purification and Disinfection by using Solar Energy: Towards Green Energy Challenge - Md Z.H. Khan; Md R. Al-Mamun; Suvash C. Majumder; Md Kamruzzaman (Aceh International Journal of Science and Technology, 2015)
The aim of this work was to design a solar water treatment plant for household purpose. Water purification is the process of eradicating detrimental chemicals, biological poisons, suspended solids and gases from contaminated water. In this work we have reported an investigation of compact filter which is cost effective for developing countries and ease of maintenance. We have arranged a solar water disinfection system that improves the microbiological quality of drinking water at household level. We get 14 L pure water and 16 ml water vapour within 240 min by using filtration method. From our work we get hot water up to 49°C. The efficiency of the system at sunny days and cloudy days are 18.23% and 18.13% respectively. This simple solar hybrid system helps to remove turbidity as well as chemical and pathogenic contaminants from water sources in the most affordable, and expedient manner possibly.